Políticas de integração na fronteira trinacional Brasil, Peru e Bolívia - OLIVEIRA, Maria do Socorro Soares de (Universidade Federal do Pará, 2013)
International borders are highly complex spaces, characterized by great diversity of ethnicities and multinational identities. In the South western Amazon there is a strategic geopolitical area, formed by the trinational frontier between Acre (Brazil), Madre de Dios (Peru) and Pando (Bolivia). Despite legitimate national security concerns, justifying the creation of a special territory along the international boundary, there is no systematic policy addressing regional specificities, from either an economic or citizenship standpoint. The physical integration of Brazil, as a core issue regarding both the national interest and the fight against illicit activities, attaches a new strategic role to international boundaries. Interest for boundaries is gaining a new momentum out of these issues, making cross-border relations a priority in international relations. Indeed, the search for new meaning to the Brazil’s interactions with its neighboring countries, has been redirecting the action of the Brazilian State, with reflections on South America’s geopolitics. The aim of this study is to analyze regional integration policies and actions in the context of the development process taking place in a trans-frontier area under the trinational jurisdiction of Brazil, Peru and Bolivia.